NOX/NADPH Oxidase, the Superoxide-Generating Enzyme: Its Transcriptional Regulation and Physiological Roles - Masato Katsuyama (Elsevier, 2010)
NADPH oxidase is a superoxide (O2−)-generating enzyme first identified in phagocytes that shows bactericidal activities. It has been reported that O2− is also produced in an NADPH-dependent manner in non-phagocytes. In the last decade, non-phagocyte-type NADPH oxidases have been identified, and the catalytic subunit NOX family has been found to be composed of five homologs, NOX1 to NOX5, and two related enzymes, DUOX1 and DUOX2. These NOX proteins have distinct features in dependency on other components for maximal enzymatic activity, tissue distribution, expressional regulation, and physiological functions. This review summarized the distinct characteristics of NOX family proteins, especially focusing on their functions and mechanisms of their expressional regulation. Keywords:: NADPH oxidase, NOX, superoxide, oxidative stress